Infectivity of human coronavirus strain 229E. - Macnaughton, M R (1980)
The replication of human coronavirus strain 229E was observed by using indirect immunofluorescence in infected monolayers of MRC continuous cells. By 8 h after infection, bright cytoplasmic fluorescence was detected in cells infected with human coronavirus 229E. Discrete foci of infection were observed from 8 to 16 h after infection in cells infected with high dilutions of human coronavirus 229E; each fluorescent focus corresponded to a single virus infection. A fluorescent focus assay is described, using indirect immunofluorescence, which is more sensitive than the established techniques of tube titration and plaque assay. Particle/infectivity ratios for unpurified and purified virus preparations revealed a considerable drop in infectivity on purification.